"Barlake" and 'Adl: Discourse Analysis Sakinah Family Education for Muslim Women's Empowerment in Eastern Indonesia - Rafi Akhsanul Kholikin; Adi Irfan Marjuqi (Anjasmoro: Islamic Interdisciplinary Journal, 2025)
The dialectical interplay between the Barlake (dowry) tradition in East Nusa Tenggara (NTT), Indonesia, and the Islamic concept of 'adl (justice), along with its implications for discourses on family well-being education and the empowerment of Muslim women. Employing a phenomenological qualitative design and critical discourse analysis involving 33 participants, the research reveals a significant commodification of Barlake, transforming it into a financial and psychological burden that contravenes the principles of maqashid al-shari'ah (the higher objectives of Islamic law). The findings indicate both philosophical convergences between the original ethos of Barlake and the values of 'adl, as well as observable societal resistance and negotiation. Non-formal Islamic education utilizing a reconciliatory-adaptive approach proved effective as a conflict mediator. As a key implication, this study formulates a Maqashid-Based Empowerment Policy for Customary Contexts (M-BEPC) framework, integrating educational, regulatory, and economic dimensions to achieve substantive justice. This research contributes to the discourse on locally-grounded Islamic education and contextual public policy innovation.